Preeclampsia-eclampsia is a multifactorial syndrome of maternal-fetal origin - Pacora, Percy (2015)
During normal pregnancy, the cytotrophoblast becomes their epithelial phenotype to endothelial phenotype (termed pseudo-vasculogenesis) and invade the maternal spiral arteries. This physiological transformation myometrial spiral arteries increases blood flow and nutrient supply to the fetus at the end of the first quarter. Vascular, such as vascular endothelial growth factor (VEGF), placental growth factor (PIGF), the tyrosine kinase-1 soluble fms-like receptor (sFlt1) factors involved in this process. At the origin of circulating angiogenic proteins involved preeclampsia. Furthermore, serum from women with preeclampsia reduced the viability of the trophoblast, which is related to changes in the sensitivity of trophoblast to Fas-mediated apoptosis, which could be mediated by proinflammatory cytokines, which have been found increased in patients with preeclampsia. In preeclompsia, there is a defective pseudovasculogénesis resulting placental ischemia and has been proposed to facilitate the release of factors derived from the placenta. Stressors intervene in isolation or simultaneously on maternal-placental / embryo-living organism. The living organism respond to stress, according to their genetic predisposition to an inflammatory response, metabolic syndrome, reduced placental perfusion, increased oxidative stress and impairment of prostacyclin / nitric oxide ratio. Therefore, hypertension is an adaptive response of the maternal-fetal unit and would be a consequence rather than the cause of the disease. Pregnancy toxemia or preeclampsia-eclampsia is a multifactorial syndrome maternal-fetal origin, varied clinical, in which blood pressure is not always present.